Intercultural perspectives on family counseling - Canfield, Brian S. (Brian Stephen) (New York : Routledge, 2020)
Intercultural Perspectives on Family Counseling expands cultural awareness in the practice of family counseling by offering cultural-specific perspectives for addressing common issues that emerge in dyadic, marital, and family relationships around the globe. The topics illuminated in the book serve to sharpen cultural mindfulness and expand the reader's knowledge and understanding of intercultural family counseling issues. Each chapter examines a couple or family-related clinical issue, offering clinical intervention strategies within the context of a specific cultural population. By representing various national and cultural identities, this book showcases a transcultural understanding of family. Students and practicing marriage and family counselors and therapists will benefit greatly from this clinical resource that exposes them to the similarities and differences in addressing client issues across cultures.
Basics of Intercultural Family Counseling Brian S. Canfield Counseling Muslim Couples and Families in the United States Khalid A. Alfallatah Family Counseling in Uganda Daniel Williamson and Jennifer Williamson Marriage Counseling with Iranian Couples Neda Deylami Counseling Greek-Cypriot Clients Fotini Kranou Kyriakides Couple Counseling in Turkey: Considering Relationship Beliefs and Gender Roles Berke Kirikkanat Stressors upon Marriage in the Barter Economy of Cuba Miriam Moreno-Duany Addressing Domestic Violence with Russian Couples Alena Prikhidko Counseling Females in the "Cajun" Culture of South Louisiana Irene Leblanc Mate Selection Counseling for Chinese Women Ruoxi Chen, Stephen E. May, Jarodd W. Hundley, and Jason P. Austin Helping Jewish Couples Address Issues of Gender Role Conflict in Marriage Ashley Cooper Marriage and Family Counseling in Saudi Arabia Abeer Ali Rasheed and Mehmet Nurullah Akkurt Familias Fuertes: Strength-Based Approaches to Working with Latino Immigrant Families E. Carolina Benitez and Daniel Gutierrez Culturally Contextual Family Therapy with Involuntary Clients Bethany Simmons and Jamie Banker Cultural Considerations for Counseling Aging Families Lori L. Soli andSusanJ.Foster Working with Taiwan Couples in Light of Culture: A Case of Mother and Daughter-in-Law Relationship Wentao Chao 17. Family Systems Therapies with Appalachian Families Jason P. Austin, Benjamin J. Evans, and Ruoxi Chen
OCLC-licensed vendor bibliographic record.
Keywords: Family counseling; Cross-cultural counseling; FAMILY & RELATIONSHIPS / General; FAMILY & RELATIONSHIPS / Conflict Resolution; PSYCHOLOGY / Psychotherapy / Counseling